2022
DOI: 10.1002/ece3.9027
|View full text |Cite
|
Sign up to set email alerts
|

Camera trap data suggest uneven predation risk across vegetation types in a mixed farmland landscape

Abstract: Ground-nesting farmland birds such as the grey partridge (Perdix perdix) have been rapidly declining due to a combination of habitat loss, food shortage, and predation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 114 publications
2
12
0
Order By: Relevance
“…Morris & Gilroy (2008) also found higher nest predation rates in yellow wagtails Motacilla flava and Eurasian skylarks Alauda arvensis that nested closer to the edge and similar patterns have been observed in Northern lapwings Vanellus vanellus (Sheldon, Chaney, & Tyler, 2007;MacDonald & Bolton, 2008). In a previous study, we also found predator activity to be higher along edges and in linear structures compared to the interior of flower blocks (Laux, Waltert, & Gottschalk, 2022). Predators frequently use edges and other linear structures as travelling lanes and may prefer field margins for hunting due to higher small mammal densities or easier accessibility compared to the denser vegetation in fields or fallows ( S alek et al, 2009Laidlaw et al, 2013;Bischof et al, 2019).…”
Section: Discussionsupporting
confidence: 83%
“…Morris & Gilroy (2008) also found higher nest predation rates in yellow wagtails Motacilla flava and Eurasian skylarks Alauda arvensis that nested closer to the edge and similar patterns have been observed in Northern lapwings Vanellus vanellus (Sheldon, Chaney, & Tyler, 2007;MacDonald & Bolton, 2008). In a previous study, we also found predator activity to be higher along edges and in linear structures compared to the interior of flower blocks (Laux, Waltert, & Gottschalk, 2022). Predators frequently use edges and other linear structures as travelling lanes and may prefer field margins for hunting due to higher small mammal densities or easier accessibility compared to the denser vegetation in fields or fallows ( S alek et al, 2009Laidlaw et al, 2013;Bischof et al, 2019).…”
Section: Discussionsupporting
confidence: 83%
“…In these complex landscapes the abundance of field‐breeders is low and particularly at risk from breeding failure due to high predation pressure at forest edges (Ludwig et al, 2012). In agricultural landscapes, predators often concentrate near woody features, and densities in non‐productive features such as sown flower strips are low, especially away from their edges (Laux et al, 2022). Therefore, fallow land might offer safe nesting sites for ground‐foraging and ground‐nesting birds such as Eurasian Skylark, while at the same time providing sufficient food resources (Berg & Pärt, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In these complex landscapes the abundance of field-breeders is low and particularly at risk from breeding failure due to high predation pressure at forest edges (Ludwig et al 2012). In agricultural landscapes, predators often concentrate near woody features, but predator densities in unproductive features such as sown flower strips are low, especially away from their edges (Laux et al 2022). Therefore, fallow land might offer safe nesting sites for ground-foraging and ground-nesting birds such as Alauda arvensis and Vanellus vanellus , while at the same time providing plentiful insect and seed resources (Berg and Pärt 1994).…”
Section: Discussionmentioning
confidence: 99%